Comparative Analysis of E-Business Implementation in Service Companies (Case Study of PT. Gojek and PT. Grab Indonesia) - Amanda Damayanti Nasution; Helva Diansyah Putri; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2022)
The implementation of an E-Business strategy increases the advantages of a business. The online motorcycle taxi service is also an application of e-business to a business where initially motorcycle taxis were only available at certain posts, but now the motorcycle taxi service can be used only by ordering via a smartphone. This study aims to determine how the comparison of companies that offer services as their products in implementing E-Business. This type of research method is qualitative by using descriptive methods and taking secondary data. The results of this study show that the concept used by online motorcycle taxis Go-Jek and Grab is the same, because these two companies offer the same services and have the same target, but the only difference is the number of services they offer and the customer satisfaction they provide. give, based on research results that Grab enthusiasts are more used than Go-Jek even though the services offered by Go-Jek are more. This online motorcycle taxi is here to make it easier for people to use motorcycle taxi services anytime and anywhere.